Water-resistant hardened geopolymer using amorphous perlite and its manufacturing method
Patent Information
- Application Number
- JP2021027067
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-24
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-02-24
AI Technical Summary
【0011】 本発明によれば、活性フィラーに、アルカリ溶液を添加し混練し養生して得られるジオポリマー硬化体において、活性フィラー及びアルカリ溶液に含まれるSiO2とAl2O3のモル比(SiO2/Al2O3)を4.0以下とすることで、ジオポリマー硬化体の吸水劣化を抑制することができると共に、10MPa以上の圧縮強度を発現することができる。
Smart Images

Figure 0007644476000008 
Figure 0007644476000009 
Figure 0007644476000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a hardened geopolymer, and in particular to a water-resistant hardened geopolymer using perlite powder (also referred to as "amorphous perlite" in this specification) containing amorphous silica as an active filler. In this specification, the "hardened geopolymer" is also referred to simply as "geopolymer." [Background technology]
[0002] In recent years, geopolymers, which are made primarily from waste and by-products, have been attracting attention as low-carbon binders. Geopolymers do not use cement clinker, but are hardened using a raw material (active filler) whose main component is amorphous aluminum silicate and at least one aqueous solution (alkaline solution) of an alkali metal silicate, carbonate, or hydroxide (see Non-Patent Document 1).
[0003] In addition to the above-mentioned alkaline solutions that have been generally used, cases have recently been reported in which alkaline alumina powder (sodium aluminate) or a mixed powder of alkaline alumina powder and sodium carbonate is used as an alkaline activator for solidifying dust (silica fume powder) generated during the manufacture of ferrosilicon, metallic silicon, electrofused zirconia, etc. (see Patent Document 1). This solidification method targets powder that is completely amorphous and has high purity silicon dioxide, and focuses only on the strength after solidification using a weak alkaline activator.
[0004] In Japan, fly ash and ground granulated blast furnace slag have been the main active fillers used in geopolymers. Ground granulated blast furnace slag in particular is widely used because it has excellent strength development properties for geopolymers. Although ground blast furnace slag contains calcium derived from limestone, the carbon dioxide (CO2) has already escaped, so the CO2 derived from limestone is not a problem in the geopolymer manufacturing process. However, like the cement industry, the use of limestone is one of the reasons for the high CO2 emissions in the steel industry. Therefore, the steel industry is also continuing to make steady efforts to reduce CO2 emissions, and with technological innovations in steelmaking, it is possible that in the future the industry will no longer use limestone and emit blast furnace slag. Therefore, a stable supply of raw materials for geopolymers must be considered.
[0005] On the other hand, perlite, a glassy volcanic rock that expands when heated, such as rhyolite, perlite, and obsidian, is virtually inexhaustible. Natural perlite contains amorphous silica (active silica) and crystalline components, and even when heated at temperatures below 800°C, the presence of amorphous silica is maintained. Therefore, amorphous perlite may be used as an active filler, which is a raw material for geopolymers (see Non-Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-19681 A [Non-patent literature]
[0007] [Non-Patent Document 1] Japan Concrete Institute: Research Committee Report on the Application of Geopolymer Technology to the Construction Industry, p.1, September 2017 [Non-Patent Document 2] ST Erdogan: Properties of ground perlite geopolymer mortars, Journal of Materials in Civil Engineering, 27(7), pp.04014210-1~10, 2015 Summary of the Invention [Problem to be solved by the invention]
[0008] However, as will be described in detail later, simply using perlite as an active filler has the problem that the resulting hardened geopolymer body undergoes deterioration due to water absorption. Therefore, the problem to be solved by the present invention is to suppress the water absorption deterioration of a geopolymer hardened body using perlite as an active filler. [Means for solving the problem]
[0009] According to one aspect of the present invention, the following 2 The hardened geopolymer and a method for producing the same are provided. 1. A geopolymer hardened body obtained by adding an alkaline solution to an active filler, kneading it, and curing it. The active filler is a perlite powder containing amorphous silica alone, or the perlite powder and Fly ash, municipal waste incineration ash molten slag powder, fluidized bed coal ash, metakaolin, sewage sludge incineration ash molten slag powder, blast furnace slag powder, or more than one of these and The alkaline solution is an aqueous solution of sodium aluminate or sodium aluminate powder plus water, or , an aqueous solution of sodium aluminate or sodium aluminate powder to which water has been added; Further, one or more of an alkali metal hydroxide, an alkali metal silicate, and an alkali metal carbonate are further included. In addition It is something that A hardened geopolymer body, in which the molar ratio (SiO2 / Al2O3) of SiO2 and Al2O3 contained in the active filler and the alkaline solution is 4.0 or less. 2. In a method for producing a geopolymer hardened body, an alkaline solution is added to an active filler, kneaded, and cured, As the active filler, a perlite powder containing amorphous silica alone or the perlite powder, Fly ash, municipal waste incineration ash molten slag powder, fluidized bed coal ash, metakaolin, sewage sludge incineration ash molten slag powder, blast furnace slag powder, or more than one of these Use something that includes The alkaline solution is an aqueous solution of sodium aluminate or a powder of sodium aluminate added with water, or , an aqueous solution of sodium aluminate or sodium aluminate powder to which water has been added;Further, one or more of an alkali metal hydroxide, an alkali metal silicate, and an alkali metal carbonate are further included. In addition Using things, A method for producing a hardened geopolymer, characterized in that the molar ratio (SiO2 / Al2O3) of SiO2 and Al2O3 contained in the active filler and the alkaline solution is 4.0 or less.
[0010] Here, the "perlite powder containing amorphous silica" in the present invention is a powder obtained by crushing natural perlite such as rhyolite, perlite, obsidian, etc., or perlite that has not been subjected to heat treatment at 800°C or higher, and contains silicon (Si 4+ In the following description, the "perlite powder containing amorphous silica" is also simply referred to as "perlite powder". Effect of the Invention
[0011] According to the present invention, in the hardened geopolymer obtained by adding an alkaline solution to an active filler, kneading and curing the mixture, the molar ratio (SiO2 / Al2O3) of SiO2 and Al2O3 contained in the active filler and the alkaline solution is set to 4.0 or less, thereby making it possible to suppress deterioration of the hardened geopolymer due to water absorption and to exhibit a compressive strength of 10 MPa or more. [Brief description of the drawings]
[0012] [Figure 1] SEM photo of perlite powder. [Diagram 2] A graph showing the effect of an alkaline solution on the strength of small rectangular column specimens of geopolymer using perlite powder. [Diagram 3] Graph showing the effect of alkaline solution on the strength of standard rectangular column specimens of geopolymer using perlite powder. [Figure 4] X-ray diffraction analysis results of perlite powder and geopolymer using perlite powder. [Diagram 5]SEM photographs of geopolymers of series WN14-NH18 shown in Table 3. [Figure 6] The distribution map of oxides of Al2O3-SiO2-Na2O was created based on the results of EDS analysis of geopolymers in the series WN14-NH18 shown in Table 3. [Figure 7] Table 3 shows the appearance of the three series of geopolymer mortars after immersion in water. [Figure 8] Graph showing flexural and compressive strength of geopolymer mortar with perlite powder and fly ash as active fillers. [Figure 9] Graph showing the effect of the sodium aluminate mixing ratio on the strength of geopolymer mortar with only perlite powder as active filler. [Figure 10] Graph showing the effect of the mixing ratio of sodium aluminate on the strength of geopolymer mortar using an active filler in which 30 mass% of perlite powder was replaced with fly ash. [Figure 11] Graph showing the effect of the mixing ratio of sodium aluminate on the strength of geopolymer mortar using an active filler in which 50 mass% of perlite powder was replaced with fly ash. [Figure 12] This figure shows the relationship between the strength and water absorption deterioration of a hardened geopolymer body using perlite powder as an active filler, and the molar ratio of SiO2 to Al2O3 (SiO2 / Al2O3) contained in the active filler and alkaline solution. [Figure 13] SEM photographs of hardened geopolymers of series FP11-AH41 shown in Table 6. [Figure 14] The distribution diagram of Al2O3-SiO2-Na2O oxides was created based on the results of EDS analysis of the hardened geopolymer body of series FP11-AH41 shown in Table 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Conventionally, geopolymers (hereinafter referred to as "GP") are generally prepared using activated fillers (hereinafter referred to as "AF") and at least one type of alkaline solution (hereinafter referred to as "AS"), which is an aqueous solution of an alkali metal silicate (such as sodium silicate or potassium silicate) or an alkali metal hydroxide (such as NaOH or KOH). In this specification, first, according to the conventional method, a GP mortar containing perlite powder as an active filler (hereinafter referred to as "perlite GP mortar") was prepared using a single or mixed solution of water glass and caustic soda solution as an alkaline solution, and its performance was examined.
[0014] 1. Preparation and performance of perlite GP mortar by conventional method 1.1 Materials used The materials used in this test are shown in Table 1. Perlite powder (hereinafter referred to as "PP") is made by dissolving granular perlite ore (coarse grain ratio 0.67, maximum particle size 0.3 mm) in a granular powder with a specific surface area of 6000 cm. 3 The PP was ground in a ball mill until it reached a molecular weight of about 1.5g. The results of X-ray fluorescence analysis (XRF) of the PP are shown in Table 2. It can be seen that the main components of the PP are SiO2 and Al2O3. An SEM photograph of the PP is shown in Figure 1. On the other hand, as AS, one of four types of aqueous caustic soda solutions (hereinafter referred to as "NH") with a molar concentration of 10 to 18 mol / L, or a mixed solution of NH and JIS No. 2 sodium silicate (hereinafter referred to as "WG") was used. In addition, washed sea sand was used as the fine aggregate for the mortar. The surface dry density of sea sand is 2.57 g / cm 3 The water absorption rate was 1.36%, the performance rate was 66.7%, and the coarse particle rate was 2.90.
[0015] [Table 1]
[0016] [Table 2]
[0017] 1.2 Preparation and curing of test specimens To save the amount of PP used, small specimens were used to study the effect of AS on the strength of perlite GP mortar. The formulation of perlite GP mortar is shown in Table 3. The materials used were weighed, and the powder and sand were placed in a plastic beaker and mixed by hand for 1 minute. Then, AS was added and mixed for 2 minutes. After mixing, the mixture was placed in a heat-resistant polyvinyl chloride resin formwork with dimensions of 2 x 2 x 10 cm and compacted with a table vibrator for 30 seconds. The top surface of the specimen was sealed with plastic wrap and placed in a drying box at 80°C for 24 hours of curing. The specimen was then left in a room until its temperature reached room temperature, and then demolded. In the sealed state, the specimen was further cured at room temperature in air at 20±3°C and RH60±5% for 24 hours. It is believed that the strength test results are affected by the dimensions of the specimen used. To clarify the strength of perlite GP mortar, standard specimens (4 x 4 x 16 cm rectangular column specimens) were prepared using series NH0 specimens with NH molar concentrations (mol / L) of 10, 16, and 18, respectively. In preparing the specimens, the powders were mixed in a mortar mixer for 1 minute, and AS was added and mixed for 2 minutes. The compaction time using a table vibrator in preparing the specimens was 60 seconds. The specimens were sealed and cured at room temperature in air for 7 days.
[0018] [Table 3]
[0019] 1.3 Measurement items and methods (1) Strength test In the case of small rectangular specimens measuring 2x2x10cm, one rectangular specimen was cut into two pieces to measure the compressive strength. The dimensions of the two pieces were 2x2x5cm. The compressive strength was calculated as the average value of the four pieces obtained by cutting the two small rectangular specimens. On the other hand, for the 4 x 4 x 16 cm standard rectangular column specimens, a bending test was first conducted using a universal testing machine with the three-point method. Next, the pieces after the bending test were used to measure the compressive strength. The bending strength was calculated as the average of the results for the three standard rectangular column specimens, and the compressive strength was calculated as the average of the results for the six standard rectangular column specimens.
[0020] (2) SEM analysis and X-ray diffraction analysis The internal structure of the hardened pearlite GP paste of series WN14 using 18 mol / L NH (without adding sand, hereafter referred to as "WN14-NH18") was observed by scanning electron microscope (SEM), and elemental analysis was also performed by EDS (energy dispersive X-ray spectrometry). In addition, to examine the chemical composition of pearlite GP, X-ray diffraction analysis (XRD) was performed on the hardened pearlite GP paste of series NH0 using only WN14-NH18 and 18 mol / L NH. The conditions for XRD analysis were as follows: X-ray output 45 kV, 200 mA, entrance slit 1.25 deg., scan speed 5 deg / min, step width 0.005 deg., scan range 5 to 60 deg.
[0021] 1.4 Test results and discussion (1) Strength of perlite GP mortar and effect of AS Figure 2 shows the results of compressive strength measurements using small rectangular column specimens. Compared to Series WN41, Series NH0 (NH only) had higher compressive strength. Series WN14 also had the highest compressive strength. These results show that there is an optimal NH ratio for strength development in pearlite GP. In other words, when the NH ratio is low, there is insufficient stimulation by AS, resulting in less element elution from PP and less reaction products of GP. On the other hand, the addition of WG reduces the amount of Si necessary for the condensation polymerization reaction of GP. 4+ Therefore, it is believed that the strength of GP can be improved by adding a small amount of WG without significantly reducing the stimulating ability of AS. Figure 3 shows the bending strength and compressive strength of pearlite GP mortar measured using a standard rectangular column specimen. It was confirmed that both bending strength and compressive strength increased with an increase in the molar concentration of NH. Judging comprehensively from the results of Figures 2 and 3, in order to produce a pearlite GP hardened body, it is necessary to make the molar concentration of NH (mol / L) 10 or more, and from the viewpoint of improving strength, it is preferable to make it 14 or more. This is because the alkaline solution consisting of WG and NH contains the Al necessary for the condensation polymerization reaction of GP. 3+ions, and PP does not react with strong alkali. 3+ This is to prevent ions from eluting.
[0022] (2) SEM and XRD analysis results of pearlite GP The XRD results of PP, WN14-NH18 series and NH0-NH18 series GP are shown in Figure 4. As shown in the figure, the XRD chart of PP (labeled as "rough perlite" in Figure 4) shows halo peaks in the range of 2θ = 15 to 35 deg, and also peaks representing crystalline compounds such as albite, borosilicate, muscovite and quartz. Therefore, PP contains both amorphous silica and crystalline matter. As PP is not a completely amorphous mineral, and crystalline matter is also present, Al 3+ It is believed that in order to elute Al, it is necessary to add NH with a molar concentration (mol / L) of 10 or more. On the other hand, in the two GP series mentioned above, a halo peak was observed in the range of 2θ=20-40 deg., and the peak of the halo peak was located at approximately 2θ=28 deg. This suggests that a non-crystalline substance different from the non-crystalline compounds in PP was formed in GP. However, some of the crystalline substances in PP were also observed in GP. In other words, it is believed that PP did not completely dissolve and react. In particular, Al 3+ The Albite containing NH0-NH18 remained in the GP. Also, it was confirmed that zeolite was formed from the GP peaks of the series NH0-NH18. Figure 5 shows an SEM photograph of GP from the WN14-NH18 series. The EDS analysis revealed that the particle in the center of the image was unreacted PP. Figure 6 shows the distribution of oxides, Al2O3-SiO2-Na2O, created based on the EDS analysis. The figure shows that the Al content in pearlite GP is extremely low, and Na2O·SiO2 gel may have formed. The halo peak in the range of 2θ=20~40deg. is thought to be due to Na2O·SiO2 gel.
[0023] (3) Deterioration of Perlite GP by water absorption When the three series of perlite GP mortars shown in Table 3 were immersed in water for one day, the mortar expanded and cracks were observed, as shown in Figure 7. The cause is not clearly understood, but it is thought to be due to the water absorption and expansion of the alkali silica gel (Na2O SiO2 gel), similar to the deterioration mechanism of alkali aggregate reaction. In other words, PP contains a lot of SiO2, which is amorphous and necessary for the hardening reaction of GP, and in a strong alkaline solution, Si 4+ In contrast, Al 3+ Even if it contains Al, it exists mostly in crystalline form, and in alkaline solution, 3+ It is believed that alkaline silica gel was generated due to insufficient elution of alkali metal silicate. In other words, from the viewpoint of strength, a GP hardened body can be produced using PP by using an aqueous solution of an alkali metal silicate (such as sodium silicate or potassium silicate) and a hydroxide (such as NaOH or KOH) as an alkaline activator. However, this GP hardened body has poor water resistance because it contains alkaline silica gel, and may break if it absorbs moisture.
[0024] On the other hand, as mentioned above, fly ash (hereinafter referred to as "FA") contains Si 4+ Not only Al +3 It is often used as an active filler for GP because it also dissolves. 3+ In order to compensate for the lack of elution of PP, GP mortar was prepared by replacing part of the PP with FA. The mix ratio of GP mortar is shown in Table 4. The FA used is JIS II type with a density of 2.29 g / cm. 3 , specific surface area is 4392 cm 2 The chemical composition of FA is shown in Table 5. The mixing method of GP mortar and the preparation and curing of the test specimens were the same as those described above. The test specimens were 4 x 4 x 16 cm in size and were subjected to sealed air curing at 80°C for 24 hours, followed by sealed air curing at 20±3°C and RH 60±5% for one day.
[0025] [Table 4]
[0026] [Table 5]
[0027] The bending and compressive strength of GP mortars using PP and FA as active fillers are shown in Figure 8. As shown in the figure, the higher the FA replacement rate, the lower the strength of the GP mortar. In other words, if the FA replacement rate is appropriately set, a GP hardened body with the required strength can be produced. However, these two series of GP mortars expanded and cracked after being immersed in water for one day. Thus, it was found that the simple addition of FA cannot completely suppress the alkali-silica reaction, and the water absorption deterioration problem of perlite GP cannot be solved. In other words, when using a conventional alkaline solution, the addition of FA does not completely suppress the alkali-silica reaction, and the problem of water absorption deterioration of perlite GP cannot be solved. 3+ Even though the dissolution of Si increases, the Si provided to the alkaline solution and PP 4+ This does not solve the problem of excess.
[0028] 2. Study of measures against water absorption and deterioration of Perlite GP In order to solve the water absorption deterioration problem of perlite GP produced by the conventional manufacturing method, a method was investigated in which a solution of NH and sodium aluminate (hereinafter referred to as "AN") was used as an alkaline solution without using sodium silicate. The AN used has a specific gravity of 1.49 g / cm 3 The components were Al2O3 (20.02%) and Na2O (18.90%). NH was used at 18 mol / L in consideration of the elution of PP. The 12 series of mortars (see Table 6) were mixed by changing the volume ratio of AN and NH and the replacement rate of FA using the method described above, and standard rectangular column specimens of 4 x 4 x 16 cm were prepared. After 24 hours of air-sealed curing at 80°C and 1 day of air-sealed curing at 20±3°C and RH60±5%, the bending and compressive strengths were measured using a universal testing machine. For the water immersion test, cylindrical specimens with a diameter of 5 cm and a height of 10 cm or small rectangular column specimens with a size of 2 cm x 2 cm x 10 cm were used. The immersion time was 1 day, and the water temperature was 20±3°C.
[0029] [Table 6]
[0030] 2.1 Strength test results Figure 9 shows the bending strength and compressive strength of GP mortar using only PP as an active filler. Since the bending strength was small, the influence of the composition of the alkaline solution was not clearly observed. However, it was found that the compressive strength increased as the volume ratio of AN to NH (AN volume / NH volume) increased. On the other hand, Figures 10 and 11 show the bending and compressive strength test results of GP mortar using 30% and 50% by mass of FA as a substitute for PP, respectively. As can be seen from Figures 9 to 11, the strength of GP mortar increased when FA was added compared to when PP was used alone. In addition, as can be seen from Figures 10 and 11, regardless of the substitution rate of FA, the compressive strength tended to increase as the volume ratio of AN to NH (AN volume / NH volume) increased, as in the case of using only PP as an active filler. This is because PP and FA, which contain a large amount of amorphous silica, contain Si. 4+ Since ions are relatively easy to dissolve, Si can be dissolved even if the alkaline stimulus is not very strong. 4+ ions are dissolved from the active filler. Therefore, the Al of the active filler is dissolved by the stimulation of strong alkali due to the increase in the NH ratio. 3+ The addition of AN promotes the dissolution of Al ions. 3+ Providing ions is favorable for the strength expression of GP.
[0031] 2.2 Deterioration state due to water immersion test Table 6 shows whether or not each series of GP mortar hardened body was deteriorated by water absorption in a water immersion test. When Series AH11 was immersed in water, surface deterioration occurred. In contrast, Series AH10, AH21, AH31 and AH41, which have a high proportion of AN, did not deteriorate. In the case of Series AH11, because of the high proportion of NH, Si was converted from PP to Si when exposed to strong alkali. 4+ A large amount of ions were dissolved, and Al provided by AN 3+ There are few ions, so Si 4+ It is believed that the excess of ions is the cause of surface deterioration. On the other hand, the test specimens of series FP37-AH11, FP37-AH12 and FP11-AH12 showed degradation due to water absorption. As with the case of series AH11, this was also due to the conversion of PP to Si by the stimulation of strong alkali. 4+ This is thought to be due to the large amount of ions eluted. Also, when comparing the FP37-AH12 and FP11-AH12 series, the effect of strong alkali on water absorption deterioration tends to become smaller as the FA replacement rate increases. This is because the amount of Al ions eluted from FA increases as the amount of FA used increases. 3+ The ion dissolution increases and excess Si 4+ Therefore, it can be said that the water absorption deterioration problem of the perlite GP hardened body can be solved by making an alkaline solution using AN alone or a mixture of AN and NH in an appropriate ratio. Figure 12 shows the relationship between the strength of the perlite GP hardened body, the presence or absence of water absorption deterioration, and the molar ratio of SiO2 to Al2O3 (SiO2 / Al2O3) contained in the active filler and the alkaline solution. Details of the series plotted in Figure 12 are shown in Table 7. That is, one series (NH018) shown in Table 3, two series shown in Table 4, and 12 series shown in Table 6, a total of 15 series, are plotted in Figure 12. From Figure 12, it was found that regardless of the addition of FA and the composition of the alkaline solution, as long as the SiO2 / Al2O3 molar ratio was 4.0 or less, the hardened pearlite GP body had a practical strength and did not deteriorate due to water absorption. The lower limit of the SiO2 / Al2O3 molar ratio is not particularly limited, but the amount of Si in the polycondensation reaction of GP is 4+ In view of the necessity of ions and the utilization of PP, the SiO2 / Al2O3 molar ratio is preferably 2.5 or more.
[0032] [Table 7]
[0033] 2.3 SEM analysis results Figure 13 shows SEM photographs of the FP11-AH41 series. Figure 14 shows the distribution of oxides, Al2O3-SiO2-Na2O, based on the results of EDS analysis. Many FA particles can be seen in the SEM images. It was found that the FA reaction remained on the surface even after heating and curing at 80°C. It is believed that the drying of the test specimens by heating and curing prevented the progress of FA ion elution. As shown in the right image of Figure 13, the surface layers of PP and FA reacted to connect the particles. It is believed that there is a good possibility that the strength of the pearlite GP hardened body can be increased by performing high-temperature steam curing, which maintains humidity. If the elution of FA increases, the amount of AN added can be reduced. Furthermore, when Figure 6 and Figure 14 are compared, it is seen that the components of the pearlite GP hardened body tend to move toward the Al2O3 side, and the Al 3+ It is believed that the increased supply of ions led to the formation of NASH gel.
[0034] 3. Summary The test results above can be summarized as follows: 1) If the material is heated and cured, it is possible to prepare a GP hardened body using amorphous perlite powder (PP) by mixing it with a commonly used alkaline solution (NH or a mixed aqueous solution of NH and WG). However, there is a problem of deterioration due to water absorption. 2) When NH or a mixed aqueous solution of NH and WG was used as an alkaline solution, the problem of water absorption and deterioration of the GP hardened body was not solved even if a part of PP was replaced by FA. 3) By using an aqueous solution of AN or a mixture of AN and NH as the alkaline solution and setting the molar ratio of SiO2 to Al2O3 (SiO2 / Al2O3) contained in the active filler and the alkaline solution to 4.0 or less, the problem of water absorption deterioration is solved and practical strength is obtained.
[0035] As described above, in the embodiment of the present invention, the active filler may be PP alone or a mixture of PP and FA. In the latter case, the material mixed with PP is not limited to FA, and one or more other activated aluminosilicate powders may be used instead of or in combination with FA. Examples of other activated aluminosilicate powders include molten slag powder from municipal waste incineration ash, fluidized bed coal ash, metakaolin, molten slag powder from sewage sludge incineration ash, and ground blast furnace slag. All of these powders have a minimum Al content in an alkaline solution. 3+ It dissolves ions.
[0036] In the embodiment of the present invention, the alkaline solution is an aqueous solution of AN alone or a mixture of AN and NH, but it may be an aqueous solution of sodium aluminate powder to which water has been added, or an aqueous solution of sodium aluminate powder and caustic soda (sodium hydroxide) powder to which water has been added. Furthermore, the alkaline solution may further contain an alkali metal silicate (sodium silicate, potassium silicate, etc.) or a carbonate (sodium carbonate, potassium carbonate, etc.). The water added to the powder of sodium aluminate or the like in the alkaline solution may be the water added to mix with the active filler in the preparation of GP. In addition, Al from active fillers 3+ From the viewpoint of ion elution, as described above, the molar concentration (mol / L) of NH when added to the alkaline solution is preferably 10 or more, more preferably 14 or more. On the other hand, the upper limit of the molar concentration (mol / L) of NH is not particularly limited, but considering the safety of the preparation work of the GP hardened body and the excessive alkaline elution from the GP hardened body, it is preferably 18 or less.
[0037] In the above embodiment, heat curing was performed at 80°C, but the temperature for heat curing is not limited to 80°C, and heat curing can be performed at, for example, 40°C or higher.
Claims
1. A geopolymer hardened body obtained by adding an alkaline solution to an active filler, kneading it, and curing it. The active filler is a single perlite powder containing amorphous silica, or the perlite powder and one or more of fly ash, municipal waste incineration ash molten slag powder, fluidized bed coal ash, metakaolin, sewage sludge incineration ash molten slag powder, and blast furnace slag powder; The alkaline solution is obtained by adding water to an aqueous solution of sodium aluminate or sodium aluminate powder, or by adding one or more of an aqueous solution of sodium aluminate or sodium aluminate powder and water to which one or more of an alkali metal hydroxide, an alkali metal silicate, and an alkali metal carbonate have been further added; The active filler and the SiO contained in the alkaline solution 2 and Al 2 O 3 Molar ratio (SiO 2 / Al 2 O 3 ) is 4.0 or less.
2. In a method for producing a geopolymer hardened body, an alkaline solution is added to an active filler, kneaded, and cured, As the active filler, a perlite powder containing amorphous silica alone or a perlite powder containing one or more of fly ash, municipal waste incineration ash molten slag powder, fluidized bed coal ash, metakaolin, sewage sludge incineration ash molten slag powder, and blast furnace slag powder is used; The alkaline solution used is an aqueous solution of sodium aluminate or an aqueous solution of sodium aluminate powder to which water has been added, or an aqueous solution of sodium aluminate or an aqueous solution of sodium aluminate powder to which water has been added, to which one or more of an alkali metal hydroxide, an alkali metal silicate, and a carbonate have been further added, The active filler and the SiO contained in the alkaline solution 2 and Al 2 O 3 Molar ratio (SiO 2 / Al 2 O 3 A method for producing a geopolymer hardened body, characterized in that the hardening coefficient is 4.0 or less.
Citation Information
Patent Citations
Concrete mixture and manufacture of chemically stable structure and product therefrom
JP1982027960A
Production of inorganic molded body
JP1994048808A
Perlite hardened form and its production
JP1997328374A
Functional material composition that contains volcanic product or volcanic product foam, and method of producing the composition
JP2013063866A
Catalytic filter for gas filtration having bonding cement containing geopolymer material
JP2013538104A